Current state of development of basic physical parameters of Canadian American National Hockey League (NHL) ice hockey players between 2015 and 2020 with regard to game position - Sigmund, M.; Prycl, D.; Dostàlovà, I. (Journal of Physical Education and Sport, 2023)
Physical parameters represent an important part of the structure of sports performance and significantly contribute to the overall performance of an ice hockey player. Basic physical parameters are also an essential part of a comprehensive player assessment both during the initial NHL draft and in further stages of a professional career. For an objective assessment, it is desirable to know the current condition of development of monitored somatic parameters with regard to the sports discipline, performance level, and gaming position. The study aimed to analyse and present the level of development of basic physical characteristics [Body Height (BH) and Body Weight (BW)] in current ice hockey players in the Canadian-American NHL, also with respect to various gaming positions. Another aim was to compare the results with relevant data of elite ice hockey players around the world. The data of 970 ice hockey players (age range: 18-42 years; 100 % male) from NHL (2019/2020 season) were analyzed [Goalkeepers (N = 87); Defenders (N = 303); Forwards (N = 580)]. Statistical data processing was performed using a single factor ANOVA and Fisher`s (LSD) post-hoc test. The level of statistical significance was tested at a level of p = 0.05; p = 0.01. Effect Size was expressed according to Cohen`s d. Current levels of monitored parameters of NHL players represent the values: BH = 185.8±5.5 cm, BW = 90.0±6.9 kg. Significant differences among positions were found for the BH (Goalkeepers > Defenders > Forwards), BW (Defenders > Goalkeepers > Forwards). The observed values represent the current level of basic physical parameters in professional ice hockey players in the NHL and can be considered reference values in this specific population group.